Developing and testing a new instrument to measure women's satisfaction with controlled ovarian stimulation treatment. (March 2013) - Roca de Bes, Montserrat; Bruna Catalán, Isidoro; Pérez Milán, Federico; Gutiérrez, José; ,
Abstract: Objectives: To develop and test a new instrument (EFESO Questionnaire) to measure satisfaction with controlled ovarian stimulation (COS) treatment. Methods : Literature review and focus groups with clinical experts provided content for the questionnaire. A preliminary version was pilot tested in 10 women to assess comprehension and relevance. The final version was administered to 606 women receiving COS. Feasibility, reliability and validity were tested by calculating the proportion of patients completing all items, by calculating Cronbach's alpha for the overall score, and by investigating whether the instrument discriminated between patients classified according to the level of overall satisfaction and response to treatment. Factor analysis was performed. Results: The final questionnaire consisted of 17 items. 91.7% of patients completed all of the items. Cronbach's alpha was 0.93, indicating excellent reliability, and the instrument was capable of discriminating between patients categorized by responses to the question on overall satisfaction with treatment and by their response to treatment. Factor analysis showed the instrument to be unidimensional. Conclusions: The EFESO questionnaire is feasible, reliable and valid for the measurement of satisfaction with treatment in patients receiving COS treatment.